Total hip resurfacing/replacement with metal-on-metal prosthesis in young patients: studying efficacy - Adil, Syed M.; Deepak, Dilip Kumar; Singh, Anuj (International Journal of Research in Orthopaedics, 2022)
Background: This prospective case series study was carried out to review the literature and compare the efficacy of usage of metal over metal prosthesis in young patients undergoing hip replacement versus conventional metal over polyethylene prosthesis. Methods: The study was conducted at tertiary care hospital of Indian armed forces with sample size of n=25, to assess early functional outcome of total hip replacement with metal-on-metal prosthesis. Analysis was carried out in terms of improvement in functional status, pain relief, achieving greater range of motion and joint stability. Results: Mean follow up period was 26 months. The average pre-op Harris hip score was 38.96. The average post-op and last follow up Harris hip score was 84.92 and 86.1. The average pre and post op Harris hip scores of the patients with Idiopathic AVN were 39.7 and 82.5 respectively and the average pre and post op Harris hip scores of the patients with post-traumatic AVN were 37.4 and 86.2. The average pre op and post op Harris hip scores of the patients with non union fracture neck of femur were 36.5 and 86.7 respectively. None of the patient had aseptic loosening, heterotopic ossification or migration of the components, stem failure. There were no cases of dislocation of prosthesis, aseptic loosening, osteolysis, heterotrophic ossification. Conclusions: This observational study demonstrated better clinical acceptability and profile of metal on metal prosthesis in young patients, having undergone hip replacement.